Effect of biomimetic tooth mousse and toothpaste on the incidence of white spot lesions during fixed appliance orthodontic treatment: A randomized clinical trial - Samar H. Assim, M.Sc.; Yassir A. Yassir, Ph.D. (Journal of Taibah University Medical Sciences, 2025)
الملخص: أهداف البحث: يرتبط استخدام الأجهزة الثابتة التقويمية ارتباطا وثيقا بفقدان مينا الأسنان للمعادن. وقد طرحت حلول عديدة إلا أنه لا يوجد اتفاق على تدخل محدد. تم تقييم تأثير منتجات كيراسبيت بيوسمالتو المحاكية للطبيعة (معجون أسنان موس التأثير الاحترافي) على تطور آفات البقع البيضاء خلال الأشهر الستة الأولى من العلاج التقويمي، مقارنةً بمعجون الأسنان التقليدي المفلور. طريقة البحث: قسم ٧۰ مريضا بتقويم الأسنان، تتراوح أعمارهم بين ۱۲ عاما فأكثر، إلى مجموعتين باستخدام مولد أرقام عشوائية حاسوبي. استخدمت المجموعة التقليدية معجون أسنان كولجيت يوميا، بينما استخدمت المجموعة المحاكية للحيوية معجون أسنان كيراسبيت بيوسمالتو المضاد للتسوس والتآكل يوميا مع وضع كيراسبيت بيوسمالتو المضاد للتسوس والتآكل لمعجون موس التأثير الاحترافي على الأسنان الأمامية في كل زيارة. تم تقييم الأفراد شهريا لمدة ستة أشهر. تم قياس تمعدن مينا الأسنان، ومؤشر البلاك المرئي، ومؤشر نزيف اللثة على الأسنان الأمامية العلوية والسفلية. تم تقييم كل سن من حيث تمعدن مينا الأسنان باستخدام قلم دياجنودنت، ونظام الكشف والتقييم الدولي للتسوس، ومؤشر جوريليك. النتائج: شمل التحليل ٦۲ مشاركا (٣۰ مشاركا تقليديا و ٣۲ مشاركا محاكيا للحيوية). كان لدى كلتا المجموعتين درجات مماثلة لقلم دياجنودنت في جميع الفترات الزمنية. كانت هناك درجات أعلى ذات دلالة إحصائية لقلم دياجنودنت بمرور الوقت في كلتا المجموعتين. لم يتم العثور على فروق ذات دلالة إحصائية بين المجموعتين فيما يتعلق بنظام الكشف والتقييم الدولي للتسوس ومؤشر جوريليك. أظهرت المجموعة التقليدية ارتفاعا ملحوظا في درجات مؤشر البلاك المرئي عند تي ۲ (بعد شهرين)، و تي ٤ (بعد أربعة أشهر)، و تي ٥ (بعد خمسة أشهر)، و تي ٦ (بعد ستة أشهر)، ودرجات مؤشر نزيف اللثة عند تي ٤، و تي ٥، و تي ٦. الاستنتاجات: لم يُظهر الاستخدام الشهري لمعجون أسنان موس التأثير الاحترافي كيراسبيت بيوسمالتو المعالج للتسوس والتآكل مع الاستخدام اليومي لمعجون كيراسبيت بيوسمالتو المُعالج للتسوس والتآكل فعالية أكبر من معجون الأسنان المفلور في ظهور آفات البقع البيضاء خلال الأشهر الستة الأولى من العلاج التقويمي. Abstract: Background: The use of orthodontic fixed appliances is strongly linked to enamel demineralization. Numerous solutions have been presented; however, the best one remains controversial. Objectives: To evaluate the effect of Biosmalto Impact Action Mousse™ (biomimetic materials) on white spot lesions (WSLs) development during orthodontic treatment. Trial design: Multicenter, parallel groups, randomized clinical trial. Methods: A computer random number generator allocated 70 orthodontic patients aged 12 or older to two groups. The control group used Colgate toothpaste daily, whereas the intervention group used Curasept toothpaste daily with the application of Curasept Biosmalto Impact Action Mousse™ to the anterior teeth every visit. The individuals were assessed monthly for six months. Enamel mineralization, visible plaque index (VPI), and gingival bleeding index (GBI) were measured on the upper and lower anterior teeth. Each tooth was assessed for enamel mineralization using the DIAGNOdent Pen, International Caries Detection and Assessment System (ICDAS), and Gorelick index (GOI). Results: The analysis included 62 participants (30 Colgate and 32 Curasept). Both groups had comparable DIAGNOdent pen scores at all time intervals. There was a statistically significant higher DIAGNOdent pen scores over time in both groups. No statistically significant differences were found between groups for ICDAS and GOI. The Colgate group had statistically significantly higher VPI scores at T2 (after 8 weeks), T4 (after 16 weeks), T5 (after 20 weeks), and T6 (after 24 weeks) and GBI scores at T4, T5, and T6. Limitations: The study findings only demonstrated the effect of biomimetic materials during six months of orthodontic treatment. Long-term effect is worth to be also evaluated. Conclusions: Monthly application of Biosmalto Impact Action Mousse™ did not seem to be more effective than fluoridated toothpaste on the development of WSLs after six months. Registration: The study was registered with ClinicalTrials.gov on July 11, 2023 (Registration No. NCT05940701).